Extractive Spectrophotometric Determination of Clomipramine - Begum, Jameelunnisa; Somasekhara Rao, Kaza; Rambabu, C. (Asian Journal of Chemistry, 2010)
Three simple and sensitive spectrophotometric methods (M1–M3) for the assay of clomipramine in pure and dosage forms based on the formation of chloroform soluble ionassociates under specified experimental conditions are described. Three acidic dyes, namely, azocarmine-G (ACG, M1), naphthalene blue 12BR (NB 12BR, M2) and naphthalene blue black (NBB, M3) are utilized. The extracts of the ion-associates exhibit absorption maxima at 540, 620 and 580 nm for methods M1, M2 and M3, respectively. Regression analysis of Beer's law plots showed good correlation in the concentration ranges 1.0–5.0, 2.0–10 and 2.0–10 μg/mL for methods M1, M2 and M3, respectively. These methods are found to be suitable for the assay of clomipramine in pharmaceutical formulations. All of the variables have been optimized and the reaction mechanisms presented. The concentration measurements are reproducible within a relative standard deviation of 1.0%.